PATH INTEGRAL QUANTIZATION OF LAGRANGIANS WITH LINEAR ACCELERATIONS - Eyad H. Hasan (European Scientific Journal, ESJ, 2014)
The Lagrangian with linear acceleration can be considered as a model of singular system. The constrained Hamiltonian systems with linear acceleration are investigated by using the Hamilton-Jacobi method. The Hamilton-Jacobi function is constructed by applying the integrability condition on this function to obtain the path integral quantization. It is shown that the equations of motion can be obtained from the action integral